The impact of sensory marketing on brand equity and repurchase intentions at buffet restaurant in Ho Chi Minh City - Ngô Thị Lan; Nguyễn Thị Huyền Ngân; Nguyễn Thị Thanh Ngân; Nguyễn Thị Ngọc Hiệp (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The research aimed to examine the impact of sensory marketing on brand equity and repurchase intentions at buffet restaurant chains in Ho Chi Minh City. The authors applied the conceptual framework of sensory marketing. They collected data using a convenience sampling method with a sample size of 385 from customers who had dined at buffet hotpot restaurants in Ho Chi Minh City. This research used PLS-SEM, which is also applied to test the appropriateness of the measurement model, structural model, and relationship between intermediate variables. Research results show that sensory marketing positively impacts brand experience and brand equity. Brand experience positively impacts brand equity and repurchase intentions. Brand equity also has a positive impact on repurchase intentions. However, sensory marketing does not impact repurchase intention. Based on the research results, the authors propose several management implications and marketing strategies to enhance the customer's brand experience, thereby increasing brand equity and repurchase intentions.